Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.3233/cbm-130364
|View full text |Cite
|
Sign up to set email alerts
|

Association between HLA-G 3'UTR 14-bp ins/del polymorphism and susceptibility to breast cancer

Abstract: Human leukocyte antigen G (HLA-G) is a non-classic major histocompatibility complex (MHC) class I molecule that is highly expressed in cancer pathologies. A 14-bp insertion/deletion polymorphism in exon 8 of the 3' untranslated region (3'-UTR) of the HLA-G gene has been suggested to be associated with HLA-G mRNA stability and the expression of HLA-G. This study aimed to evaluate the association of 14-bp ins/del polymorphism in HLA-G gene and breast cancer in a south-east Iranian population. This study was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 38 publications
4
33
2
1
Order By: Relevance
“…There is growing documents to support the viewpoint that some miRNA specifically regulate HLA-G expression by targeting its 3´UTR (Veit and Chies, 2009;Manaster et al, 2012). The 14 bp deletion allele has been associated with high expression of HLA-G mRNA, whereas The 14 bp Ins allele (5'-ATTTGTTCATGCCT-3') has been associated with low expression of HLA-G and low production of most mRNA isoforms (Hviid et al, 2004;Martelli et al, 2013;Jeong et al, 2014) The 14bp InDel polymorphism has been extensively studied in many different publications (Moon et al, 2011;Eskandari et al, 2013). In research on south-east Iranian population, suggest that the 14-bp InDel polymorphism in HLA-G gene could be a genetic risk factor for the susceptibility to breast carcinoma (Eskandari et al, 2013).…”
Section: -Bp Insertion/deletion Polymorphism Of the Hla-g Gene In Bmentioning
confidence: 98%
See 2 more Smart Citations
“…There is growing documents to support the viewpoint that some miRNA specifically regulate HLA-G expression by targeting its 3´UTR (Veit and Chies, 2009;Manaster et al, 2012). The 14 bp deletion allele has been associated with high expression of HLA-G mRNA, whereas The 14 bp Ins allele (5'-ATTTGTTCATGCCT-3') has been associated with low expression of HLA-G and low production of most mRNA isoforms (Hviid et al, 2004;Martelli et al, 2013;Jeong et al, 2014) The 14bp InDel polymorphism has been extensively studied in many different publications (Moon et al, 2011;Eskandari et al, 2013). In research on south-east Iranian population, suggest that the 14-bp InDel polymorphism in HLA-G gene could be a genetic risk factor for the susceptibility to breast carcinoma (Eskandari et al, 2013).…”
Section: -Bp Insertion/deletion Polymorphism Of the Hla-g Gene In Bmentioning
confidence: 98%
“…The 14 bp deletion allele has been associated with high expression of HLA-G mRNA, whereas The 14 bp Ins allele (5'-ATTTGTTCATGCCT-3') has been associated with low expression of HLA-G and low production of most mRNA isoforms (Hviid et al, 2004;Martelli et al, 2013;Jeong et al, 2014) The 14bp InDel polymorphism has been extensively studied in many different publications (Moon et al, 2011;Eskandari et al, 2013). In research on south-east Iranian population, suggest that the 14-bp InDel polymorphism in HLA-G gene could be a genetic risk factor for the susceptibility to breast carcinoma (Eskandari et al, 2013). The meta-analysis study suggested that HLA-G 14-bp InDel polymorphism might contribute to breast cancer susceptibility and overall cancer risk among Asians (Yz et al, 2014).…”
Section: -Bp Insertion/deletion Polymorphism Of the Hla-g Gene In Bmentioning
confidence: 99%
See 1 more Smart Citation
“…T cells play a central role in immune protection which recruits neutrophils, eosinophils, and basophils to sites of infection and inflammation, to help B cells make antibodies, to induce macrophages to develop enhanced microbicidal activity, and through their production of cytokines and chemokines, to orchestrate the full panoply of immune responses [7]. Thereby, lot of studies demonstrated that there is close relationship between the HLA gene polymorphisms and infection disease, cancer, inflammatory, and autoimmune disease [8][9][10][11][12][13]. In addition, growing studies found that the HLA Class II gene, especially HLA-DRB1 gene polymorphisms, might significantly influence of TB risk [14][15][16], but the results have been inconclusive.…”
Section: Introductionmentioning
confidence: 97%
“…Genetic and environmental factors are involved in BC pathogenesis; however, its exact etiology is complicated and not clearly identified (5). A previous study demonstrated that genetic factors are important in the development of BC in populations in the southeast of Iran (6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%